Representation of Ampang Limo Myth Through Journalistic Photography - Mardiansyah, Andri; Sastra , Andar Indra (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose – Ampang Limo not only plays an important role as an apex predator in the tropical forest ecosystem, but also has deep spiritual and cultural dimensions. It is revered as a symbol of strength and courage in various myths, and is considered to have supernatural powers. This study explores the mythical representation of Ampang Limo, the local name for the Sumatran Tiger in Minangkabau, through journalistic photography Methodology/approach – This study uses a qualitative approach with a phenomenological method to understand the meaning behind the narrative of the Ampang Limo myth. Data were collected through interviews, observations, and documentation Findings – It was found that journalistic photography can be an effective visual medium to illustrate the relationship between reality and mythology, strengthen cultural narratives, and encourage the preservation of this species Novelty/value – The integration of phenomenological approaches and visual exploration, especially photojournalism, has not been widely used in the study of mythology and the conservation of the Sumatran tiger.